Improving Employees' Performance Through Creating a Conducive Spiritual Environment in The Workplace - Riyadi, Sugeng Ahmad; Anggraini, Diba Aris (Jurnal Riset Bisnis dan Investasi, 2021)
Many people think improving everything always has to do with material things and neglects spiritual things. Even though spiritual matters also significantly influence something in life, including something related to employee performance. This study aims to analyze the effectiveness of creating a conducive spiritual environment in the workplace on employee performance in achieving organizational goals. A total of 300 targeted questionnaires were distributed to employees in the Jabodetabek area using simple random sampling and obtained 379 complete responses from respondents. Data analysis was performed using descriptive statistical methods, correlational, and regression with the help of SPSS software. The results showed that the conducive spiritual environment in the workplace contributes positively to employees' performance. This research is expected to contribute in the form of positive conclusions and recommendations, for the academic world and the industrial world.